Progestin-primed ovarian stimulation vs mild stimulation in women with advanced age above 40: a retrospective cohort study - Qian Peng; Xiang Cao; Jing Wang; Lin Wang; Jun Xu; Xiaowei Ji; Suying Liu; Jin Zhu; Xi Dong (Reproductive Biology and Endocrinology, 2019)
Abstract Background Previous studies have demonstrated that progestin-primed ovarian stimulation (PPOS) protocol was a feasible and efficient method in in vitro fertilization (IVF) cycle. However, its application in women with advanced age has not been determined yet. The purpose of this study was to investigate its efficacy in women aged ≥40 years old. Methods This retrospective cohort study included patients with ages of ≥40 years old at the time of ovarian stimulation. The embryonic and clinical outcome of mild stimulation and PPOS were compared. Primary outcome was top-quality embryo rate on day 3, and secondary outcome was clinical pregnancy rate. Results Baseline characteristics of patients was similar in mild stimulation (122 cycles) and PPOS (47 cycles). No significant difference was found in the number of retrieved and mature oocytes and the fertilization and cleavage rates. Of interest, the rate of top-quality embryos was significantly higher in PPOS group (50.08% vs 33.29%, p = 0.015), with an increasing trend of viable embryo rate (73.55% vs 61.16%). A greater amount of gonadotropin was observed in PPOS group (2061.17 ± 1254.63 IU vs 1518.14 ± 547.25 IU, p < 0.05) in spite of comparable duration of stimulation. After FET cycle, no significant difference was found in the clinical pregnancy rates between mild stimulation (12.5%) and PPOS group (16.7%). Conclusions Higher percentage of top-quality embryos on Day 3 and comparable clinical pregnancy rate was obtained in PPOS protocol, which could be considered as a feasible ovarian stimulation protocol in women aged above 40 years old.